AN IOT-BASED WEARABLE SENSOR SYSTEM FOR MONITORING THE HEALTH, RUMINATION, AND ESTRUS CYCLE OF DAIRY COWS IN INDONESIA - Nisreen Al-Sayid; Nour Ibrahim; Hassan Al-Attar (Techno Agriculturae Studium of Research, 2025)
The rapid development of Internet of Things (IoT) technology offers significant opportunities for improving livestock management, especially in dairy farming systems in developing countries like Indonesia. Traditional methods of monitoring dairy cow health, behavior, and estrus cycles rely on manual observation, which can be time-consuming, subjective, and inaccurate. These limitations lead to delayed disease detection, suboptimal reproductive performance, and reduced milk productivity. This study aims to design and evaluate an IoT-based wearable sensor system for continuous monitoring of dairy cow health, rumination patterns, and estrus cycles in Indonesian dairy farms. A research and development approach combined with field testing was employed. The system integrates wearable sensors attached to cows, collecting data on movement, body temperature, and rumination activity. Data is transmitted in real-time via IoT networks to a cloud platform for processing and visualization. System performance was assessed through accuracy testing, reliability analysis, and farmer feedback. The results show that the system effectively detects changes in rumination behavior, identifies early health issues, and predicts estrus cycles with high consistency compared to traditional methods. Farmers reported improved decision-making efficiency and reduced labor intensity. The IoT-based wearable sensor system demonstrates potential as an innovative solution for enhancing dairy cow health monitoring and reproductive management in Indonesia, supporting sustainable dairy farming practices.